Activation-Associated Accelerated Apoptosis of Memory B Cells in Critically Ill Patients With Sepsis. Issue 5 (May 2017) - Shankar-Hari, Manu; Fear, David; Lavender, Paul; Mare, Tracey; Beale, Richard; Swanson, Chad; Singer, Mervyn; Spencer, Jo
Abstract : Objective: Sepsis is life-threatening organ dysfunction due to dysregulated host responses to infection. Current knowledge of human B-cell alterations in sepsis is sparse. We tested the hypothesis that B-cell loss in sepsis involves distinct subpopulations of B cells and investigated mechanisms of B-cell depletion. Design: Prospective cohort study. Setting: Critical care units. Patients: Adult sepsis patients without any documented immune comorbidity. Interventions: None. Measurements and Main Results: B-cell subsets were quantified by flow cytometry; annexin-V status identified apoptotic cells and phosphorylation of intracellular kinases identified activation status of B-cell subsets. B cell–specific survival ligand concentrations were measured. Gene expression in purified B cells was measured by microarray. Differences in messenger RNA abundance between sepsis and healthy controls were compared. Lymphopenia present in 74.2% of patients on admission day was associated with lower absolute B-cell counts (median [interquartile range], 0.133 [0.093–0.277] 10 9 cells/L) and selective depletion of memory B cells despite normal B cell survival ligand concentrations. Greater apoptotic depletion of class-switched and IgM memory cells was associated with phosphorylation of extracellular signal-regulated kinases, implying externally driven lymphocyte stress and activation-associated cell death. This inference is supported by gene expression profiles highlighting mitochondrial dysfunction and cell death pathways, with enriched intrinsic and extrinsic pathway apoptosis genes. Conclusions: Depletion of the memory B-cell compartment contributes to the immunosuppression induced by sepsis. Therapies targeted at reversing this immune memory depletion warrant further investigation. Abstract : Supplemental Digital Content is available in the text.